The impact of cardiac rehabilitation on lifestyles, psychological correlates and the clinical course of cardiac disease - Gostoli, Sara <1982> (Alma Mater Studiorum - Università di Bologna, 2013)
Objectives: The aim of this research was to evaluate the impact of Cardiac Rehabilitation (CR) on risky lifestyles, quality of life, psychopathology, psychological distress and well-being, considering the potential moderating role of depression, anxiety and psychosomatic syndromes on lifestyles modification. The influence of CR on cardiac morbidity and mortality was also evaluated. Methods: The experimental group (N=108), undergoing CR, was compared to a control group (N=85) of patients affected by cardiovascular diseases, not undergoing CR, at baseline and at 1-month, 6- and 12-months follow-ups. The assessment included: the Structured Clinical Interview for DSM-IV, the structured interview based on Diagnostic Criteria for Psychosomatic Research (DCPR), GOSPEL questionnaire on lifestyles, Pittsburgh Sleep Quality Index, Morisky Medication Adherence Scale, MOS 36-Item Short Form Health Survey, Symptom Questionnaire, Psychological Well-Being Scale and 14-items Type D Scale. Results: Compared to the control group, CR was associated to: maintenance of the level of physical activity, improvement of correct dietary behaviors and stress management, enhancement of quality of life and sleep; reduction of the most frequently observed psychiatric diagnoses and psychosomatic syndromes at baseline. On the contrary, CR was not found to be associated with: healthy dietary habits, weight loss and improvement on medications adherence. In addition, there were no relevant effects on sub-clinical psychological distress and well-being, except for personal growth and purpose in life (PWB). Also, CR did not seem to play a protective role against cardiac recurrences. The presence of psychosomatic syndromes and depressive disorders was a mediating factor on the modification of specific lifestyles. Conclusions: The findings highlight the need of a psychosomatic assessment and an evaluation of psychological sub-clinical symptomatology in cardiac rehabilitation, in order to identify and address specific factors potentially associated with the clinical course of the heart disease. === Obiettivi: Lo scopo della presente tesi di dottorato è stato valutare l’impatto della Riabilitazione Cardiologica (RC) sulla modificazione di stili di vita, qualità di vita, psicopatologia, distress e benessere psicologico, considerando il possibile effetto moderatore di disturbi depressivi, ansiosi e sindromi psicosomatiche sul cambiamento degli stili di vita. È stata inoltre valutata l’influenza della RC su morbilità e mortalità cardiaca. Metodi: Il gruppo sperimentale (N=108), sottoposto a RC, è stato confrontato con un gruppo di controllo (N=85), composto da pazienti cardiopatici non sottoposti a RC, sia alla baseline che a 1 mese, 6 e 12 mesi. L’assessment ha incluso: la Structured Clinical Interview for DSM-IV, l’intervista strutturata basata sui Diagnostic Criteria for Psychosomatic Research (DCPR), il questionario GOSPEL sugli stili di vita, il Pittsburgh Sleep Quality Index, la Morisky Medication Adherence Scale, il MOS 36-Item Short Form Health Survey, il Symptom Questionnaire, la Psychological Well-Being Scale e la 14-items Type D Scale. Risultati: La RC, rispetto alla condizione di controllo, è risultata associata a: mantenimento dei livelli di attività fisica, aumento dei comportamenti alimentari corretti e della capacità di gestione dello stress, miglioramento della qualità di vita e del sonno; diminuzione delle diagnosi psichiatriche e psicosomatiche più frequentemente riscontrate alla baseline. Al contrario, non è risultata associata a: stile alimentare sano, perdita di peso e miglioramento dell’aderenza farmacologica. Inoltre, non sono stati riscontrati effetti rilevanti riguardo a benessere e distress psicologico sub-clinico, fatta eccezione per la crescita personale e lo scopo nella vita (PWB). La RC non ha inoltre svolto un ruolo protettivo sul decorso clinico. La presenza di sindromi psicosomatiche e disturbi depressivi ha influenzato l’andamento di specifici stili di vita. Conclusioni: I risultati evidenziano l’importanza di una valutazione psicologica integrata in riabilitazione cardiologica, allo scopo di identificare e gestire fattori potenzialmente associati al decorso clinico della patologia cardiaca.